Achievements and lessons learned from the 32-year old Canada-U.S. effort to restore Impaired Beneficial Uses in Great Lakes Areas of Concern. Issue 4 (2nd October 2018) - Hartig, J.H.; Krantzberg, G.; Munawar, M.; Doss, M.; Child, M.; Kalinauskas, R.; Richman, L.; Blair, C.
Abstract : Since 1985, governments and stakeholders have been developing and implementing remedial action plans to restore beneficial use impairments in polluted areas of the Great Lakes called Areas of Concern. Initially, progress was slow because of severity and geographic extent of the problems, lack of clarity on use of an ecosystem approach, time commitments for effective involvement of stakeholders, evolution of management programs, and need to secure restoration funding. Over time, many of these constraints have been overcome. Presently, as of 2017, seven Areas of Concern have been delisted, two have been designated as Areas of Concern in Recovery, and 18 have implemented all remedial actions deemed necessary for use restoration. Although progress has been made, much remains to be done to restore all impaired uses and delist all Areas of Concern. Notable achievements include: use of an ecosystem approach and requisite governance frameworks, contaminated sediment remediation, habitat rehabilitation, and control of eutrophication. Lessons learned are presented to help complete the cleanup of Areas of concern and help others restore degraded aquatic ecosystems worldwide.